Bacteriocinogenic Lactic Acid Bacteria of Caprine Products from Chaco-Argentina - Rivas, Franco Paolo (2014)
The microbiota of artisanal caprine products is essential for the manufacture of fermented products, such as cheeses and dry sausages, conferring them particular and distinctive flavors and generating high value-added products. Many of the bacteria comprising this microbiota are able to produce bacteriocins and antimicrobial substances. The finding of bacteriocinogenic strains within this microbiota could be the first step to introduce biopreservation into these products. Hence, ten lactic acid bacteria (LAB) (6 Lactobacillus paracasei, 2 Lactococcus lactis, 1 Leuconostoc mesenteroides and 1 Lactobacillus rhamnosus) isolated from artisanal caprine products from Chaco (Argentina) were screened for antagonistic activity against other LAB and some spoilage and pathogenic microorganisms, such as Listeria innocua (in lieu of Listeria monocytogenes), Staphylococcus aureus and Escherichia coli. The final goal was to investigate LAB antibacterial activity within this unexplored ecological niche and to select interesting strains for the role of bio-preservatives. Bacteriocin-like substances (BLIS) produced by the isolated strains inhibited three species of S.aureus, L. innocua and Brochothrix thermosphacta. Titles of these antibacterial substances were within the range 100- 200 AU.mL-1. BLIS produced by the isolated strains were heat stable and effective after refrigerated storage and freeze/thaw cycles. Moreover, BLIS activity was higher at acidic pH values, showing a decrease when these values were closer to neutrality or they become alkaline. BLIS did not adsorb to the producer cells which is expected for future production and application on food systems. The results presented in this study could contribute to characterize the antimicrobial activity of the indigenous flora of artisanal caprine products manufactured in the province of Chaco,Argentina. The isolated bacteriocinogenic strains showed a regular production of BLIS in culture broth, which offers promising applications for the biopreservation of these products.